(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Cerebral venous sinus thrombosis (CVST) is a fatal condition if not treated accordingly. As it has a wide variety of presentations & association with many other diseases, often we felt diagnostic dilemmas & challenges. This consumes our time as well as put a bad impact on patient’s recovery. As like many other inflammatory conditions, Inflammatory Bowel disease (IBD) has also association with venous thromboembolism (VTE)1. Usually VTE’s are associated with the flare of IBD2. The common sites are deep veins of legs, pulmonary veins, portal veins & mesenteric veins3. Although not so common still there are some case reports regarding CVST in Crohn’s disease (CD) patients like ours one. A 31 years old lady diagnosed as a case of Crohn’s disease 1 year earlier presented with headache, vomiting, left sided hemiparesis & several episodes of convulsion. Magnetic resonance imaging (MRI) of the brain with venography showed venous thrombosis superior sagittal sinus. Then she was immediately anticoagulated with low Molecular weight heparin (LMWH) followed by Rivaroxaban 20mg daily. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):92-95